المنظومة العقائدية والفكرية للمعتزلة في االصول الخمسة - عبدالرحمن صديق محمد (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
Significant of research include the origin Mu̓ tazila statement and the reasons for their isolation and named this term and the most important of their beliefs in the five assets. It is worth mentioning ideological school based on the mind only, and ideas that took from Greek philosophy which differentiated views with the Sunna group in most ideological matters and individual approach among all doctrines for adoption the Islamic. It dealt with the search for the statement and to clarify the differences and right opinion, and ask the God to help me for serving and giving benefit and if it is wrong to me and ask His forgiveness of God and repent to Him.